2013
DOI: 10.1007/s11892-013-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Diabetes-Related Cardiovascular Disease: Systematic Review of Published Evidence from Observational Studies and Clinical Trials

Abstract: The cost of treating cardiovascular disease (CVD) and diabetes is enormous and is set to rise in the coming years. Physical inactivity and sedentary behaviors are major risk factors for these diseases and are estimated to account for several million global deaths annually. Lifestyle interventions, particularly those aimed at enhancing physical activity levels, have a substantial favorable impact on diabetes progression in people at high risk of the disease. Although observational studies and small intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…While exercise and lifestyle choices are the best preventative measures for the conditions(65,66), the SGLT2 inhibitors hold promise as effective treatment for both data suggests that the inhibitors are moderately effective at reducing blood pressure, and trials are underway to see if these drugs' antidiabetic and antihypertensive properties translate into cardiovascular benefit. At the same time, the SGLT2 inhibitors elucidate the link between the metabolic, pathologic, and hemodynamic derangements of diabetes.Continued research into mechanisms underlying this drug class's antihypertensive effect could provide insight into the pathophysiology of diabetic nephropathy and diabetes-related hypertension as well as suggest new drug targets for all these conditions.…”
mentioning
confidence: 99%
“…While exercise and lifestyle choices are the best preventative measures for the conditions(65,66), the SGLT2 inhibitors hold promise as effective treatment for both data suggests that the inhibitors are moderately effective at reducing blood pressure, and trials are underway to see if these drugs' antidiabetic and antihypertensive properties translate into cardiovascular benefit. At the same time, the SGLT2 inhibitors elucidate the link between the metabolic, pathologic, and hemodynamic derangements of diabetes.Continued research into mechanisms underlying this drug class's antihypertensive effect could provide insight into the pathophysiology of diabetic nephropathy and diabetes-related hypertension as well as suggest new drug targets for all these conditions.…”
mentioning
confidence: 99%
“…A recent review of exercise and diabetes-related CVD identified nearly 100 published studies from the last decade, concluding that it is unclear why lifestyle intervention in people with diabetes reduces established CVD risk factor levels but have no obvious effect on CVD event rates [38]. However, healthy lifestyle behaviors may positively impact CVD event rates by reducing glucose toxicity, something glucose-lowering drugs do not achieve [38]. Exercise training ameliorates adverse vascular changes including endothelial dysfunction and arterial remodeling and stiffness, changes that are typically present during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It improves the redox state through the absolute increase in nitric oxide concentrations, making nitric oxide bioavailable for the reduction of oxidative compounds found in cardiometabolic diseases [39,40]. Interestingly, the legacy effect of exercise (protective effect even after exercise is stopped) observed in the prevention of diabetes is not apparent in the prevention of CVD events [38].…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Hence, it was of interest to investigate the relationship of the diabetes ORFs with other diseases. The diabetes ORFs from the GAD were analyzed using the MeSH and the broad terms filters.…”
Section: Association Of the Diabetes Orfs With Diverse Diseasesmentioning
confidence: 99%